2021
DOI: 10.1155/2021/8893679
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐Dependent Glucose Transport in Skeletal Muscle by Diphlorethohydroxycarmalol, an Alga Phlorotannin: In Vitro and In Vivo Study

Abstract: Diphlorethohydroxycarmalol (DPHC), a type of phlorotannin isolated from the marine alga Ishige okamurae, reportedly alleviates impaired glucose tolerance. However, the molecular mechanisms of DPHC regulatory activity and by which it exerts potential beneficial effects on glucose transport into skeletal myotubes to control glucose homeostasis remain largely unexplored. The aim of this study was to evaluate the effect of DPHC on cytosolic Ca2+ levels and its correlation with blood glucose transport in skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Our hypothesis is based on previous reports which suggested that IO extract and its active component DPHC can enhance glucose homeostasis and that the protein level is related to muscle contraction and improves myopathy in skeletal muscle cells in vitro [3,5,6]. Although the potential of IO extract and its active component DPHC for treating muscle atrophy has been suggested, an in vivo study of skeletal muscle atrophy to evaluate the effect of IO extract and its active component DPHC and its related properties in skeletal muscle function is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis is based on previous reports which suggested that IO extract and its active component DPHC can enhance glucose homeostasis and that the protein level is related to muscle contraction and improves myopathy in skeletal muscle cells in vitro [3,5,6]. Although the potential of IO extract and its active component DPHC for treating muscle atrophy has been suggested, an in vivo study of skeletal muscle atrophy to evaluate the effect of IO extract and its active component DPHC and its related properties in skeletal muscle function is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Brown alga, Ishige okamurae (IO), and its prominent component diphlorethohydroxycarmalol (DPHC) have been studied in various rodent models to investigate their therapeutic activity against type 2 diabetes mellitus, hyperlipidemia, and hypercholesterolemia, due to their exceptional oral bioavailability [1,2]. Additionally, their activity on glucose homeostasis in skeletal myotubes has been reported earlier, suggesting that IO extract and its active component DPHC could activate glucose transport into the skeletal muscle, thereby improving glucose homeostasis and inducing energy expenditure by muscle contraction [3]. In addition to these reports of DPHC acting on the skeletal muscle, a recent investigation has reported its benefits against the inflammatory response of myopathy in skeletal muscle [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The balance between calcium distribution through calcium-permeable membrane channels (including TRPV channels) and transmembrane channels is needed for proper calcium signalling [ 45 ], and dysregulated calcium signal transduction is associated with many medical conditions including IR and T2DM [ 114 ]. Calcium signalling regulates glucose metabolism by stimulation of GLUT4 movement and, eventually, glucose uptake through insulin-dependent and independent signalling pathways [ 115 , 116 ]. Insulin mediates calcium flux from both extracellular space and ER in the cells.…”
Section: Calcium Signalling: the Potential Common Pathway Between Cap...mentioning
confidence: 99%
“…An increase in cytosolic calcium concentration in skeletal muscle cells leads to phosphorylation of CAMKK2, which upregulates GLUT4 [28]. To examine the effect of capsaicin or ZnSO 4 + NaPy on the phosphorylation status and activation of CAMKK2, skeletal muscle cells were treated with 100 µM capsaicin or 20 µM ZnSO 4 + 10 µM NaPy over 60 min (Figure 3).…”
Section: Capsaicin and Zinc Phosphorylate Camkk2 In C2c12 Skeletal Mu...mentioning
confidence: 99%
“…Calcium is a ubiquitous second messenger regulating signalling pathways involved in glucose homeostasis in skeletal muscle [25][26][27]. Increased cytosolic calcium levels activate intracellular signalling molecules including CAMKK2 [28] and its downstream proteins including CREB and TORCs [29][30][31][32]. Activation of CREB and TORC1 promotes glucose uptake in skeletal muscle cells by regulating the expression of genes associated with glucose metabolism which include activating transcription factor 3 (Atf3), V-jun avian sarcoma virus 17 oncogene homolog B (Junb), and nuclear receptor 4 A3 (Nr4a3) [33,34].…”
Section: Introductionmentioning
confidence: 99%